An introduction to graphical methods in data analysis - Jones, Peter, 1943- (Deakin University : distributed by Deakin University Press, 1993)
"This book has been produced as part of the study materials for ECS808 Applied statistics, which is one of the units offered by the Faculty of Education in Deakin University's Open Campus Program."--T.p. verso.